Classification and quantification of initial porosity in a CMC laminate - Del Puglia, Paolo; Sheikh, Mohammed A.; Hayhurst, David R. (Composites. Part A, Applied science and manufacturing, 2004)
This paper examines the classification and quantification of initial or manufacturing porosity of a 10 layer laminate ceramic matrix composite DLR-XT. Both optical and scanning electron microscopy (SEM) techniques are used to identify different classes of porosity and to measure and quantify their extent. Four classes of porosity have been identified, namely inter-fibre micro-porosity; trans-tow cracks; matrix cracks; and denuded matrix regions. The presence of each of these types of porosity has been confirmed by both optical and SEM examination. In order to quantify the degree of porosity, two approaches have been used. For the case of void-like porosity, area fraction has been used; and, for crack-like porosity, the periodicity of the cracks and their lengths has been measured. The paper concludes by tabulating porosity types and their levels observed. No interpretation is made of the significance of these magnitudes since this will be subsequently carried out in the context of their influence on thermal and mechanical properties. This will form the subject of a series of subsequent papers.